Traditional Criminal Law Existence in the Settlement of Criminal Action in the Environmental Field in Indonesia - Bambang Hartono, Mohamad Syarhan, Nyoman Serikat Putra Jaya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Many cases of environmental pollution and illegal logging have caused alarming damage to the environment. In the Law regarding Environmental Protection and Management, tools to protect the environment have been regulated. One of which is the application of criminal sanctions, but in Indonesia, some laws live in society, one of which is customary criminal law which can also solve criminal acts in the environmental sector. This research aims to analyze the existence of customary criminal law in the settlement of crimes in the environmental sector. This research is legal research with normative juridical research. The results of this study will be presented in descriptive form. The results showed that Hulsman said the criminal justice system had caused suffering because it could not work according to its objectives and did not carry out the principle of accountability. This judicial system had innate defects. In settlement of criminal acts in the environmental sector, examples of customary criminal law are the settlement of fish poisoning cases committed by some Paya Village Village residents. They use fish poison from plants (tuba), Lannet in the form of flour, Bistox in liquid, and Decis, which is liquid.